Implementation of Playing and Sports Infrastructure at Madrasah Aliyah Nahdlatul Ulama Buntet Islamic Boarding School in Cirebon - Nurfaizah; Hendra Purwanto; Nur Mahmudi Ismail; Nur Fitria (Quality : Journal Of Education, Arabic And Islamic Studies, 2023)
This research was to determine the implementation of playing and sports infrastructure at Madrasah Aliyah Nahdlatul Ulama (MANU) Putra Buntet Islamic Boarding School Cirebon, supporting the implementation of sports learning. This research is a descriptive study with qualitative methods, data analysis using interactive analysis techniques which include data reduction, presentation  data and drawing conclusions.  For the validity of the data using triangulation techniques.  The results of the study show that the condition of the facilities and infrastructure for each sport is not the same, both for gymnastics, athletics, football, sepaktakraw, volleyball, basketball, table tennis, self-defense and swimming.  It was concluded that of all the physical education facilities and infrastructure for MANU Putra buntet pesantren Cirebon, a percentage of 70% was found in the ideal category, in accordance with the infrastructure standards set out in Permendiknas Number 24 of 2007.